2002
DOI: 10.1002/cne.10242
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical studies of period gene expression in the hawkmoth, Manduca sexta

Abstract: In the nervous system of the hawkmoth, Manduca sexta, cells expressing the period (per)gene were mapped by in situ hybridization and immunocytochemical methods. Digoxigenin-labeled riboprobes were transcribed from a 1-kb M. sexta per cDNA. Monoclonal anti-PER antibodies were raised to peptide antigens translated from both M. sexta and Drosophila melanogaster per cDNAs. These reagents revealed a widespread distribution of per gene products in M. sexta eyes, optic lobes, brains, and retrocerebral complexes. Labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(159 citation statements)
references
References 85 publications
(114 reference statements)
8
146
1
4
Order By: Relevance
“…While it can be argued that in some of these studies perhaps the antigenicity did not reflect PER in these insects, or that PER does indeed enter the nucleus at low undetectable levels to engage the negative feedback loop, it is odd that PER antigenicity, whether cycling in the firebrat (Zavodska et al 2003a) or not in the hawkmoth (Wise et al 2002) or the beetle (Frisch et al 1996), or ''not known'' in a variety of other insects (Zavodska et al 2003b), does not usually appear to be nuclear. In fact, on the basis of our initial results with Musca, we might have been tempted to add the housefly to the list of species with ''noncanonical'' patterns of PER regulation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While it can be argued that in some of these studies perhaps the antigenicity did not reflect PER in these insects, or that PER does indeed enter the nucleus at low undetectable levels to engage the negative feedback loop, it is odd that PER antigenicity, whether cycling in the firebrat (Zavodska et al 2003a) or not in the hawkmoth (Wise et al 2002) or the beetle (Frisch et al 1996), or ''not known'' in a variety of other insects (Zavodska et al 2003b), does not usually appear to be nuclear. In fact, on the basis of our initial results with Musca, we might have been tempted to add the housefly to the list of species with ''noncanonical'' patterns of PER regulation.…”
Section: Discussionmentioning
confidence: 95%
“…observation that, in several insect orders, PER can be found to be exclusively cytoplasmic in its neuronal expression is inconsistent with its ''dedicated'' role as a circadian transcriptional regulator. One group of ''neuronal'' cells that do show nuclear expression of PER are the photoreceptors of both the giant silkmoth A. pernyii and the hawkmoth Manduca sexta where cycles in PER immunoreactivity have been documented in the former species, but not in the latter Wise et al 2002). However, in the hawkmoth, nuclear staining of PER was consistently observed in four neurons within each hemisphere in the pars lateralis, a neurosecretory region, although no circadian cycling of PER abundance was noted (Wise et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of PER subcellular localization in Drosophila differs dramatically from that of A. pernyi and most other insects (15,16). The tobacco hawkmoth, Manduca sexta, is also atypical in that PER nuclear immunostaining (but not PER rhythmicity) is readily detectable in brain neurons (51). However, regardless of how PER subcellular transport is controlled, a Drosophila-like feedback loop may form the core of the circadian clockwork in insects.…”
Section: Figmentioning
confidence: 96%
“…1; see review Žitňan and Adams, 2005) and corazonin immunoreactivity was detected in brain lateral neurosecretory cells in representatives of most major insect orders, except beetles (Veenstra and Davis, 1993;Cantera et al, 1994;Hansen et al, 2001;Roller et al, 2003). In moths these corazonin lateral cells also express the circadian clock protein period (PER) involved in the regulation of circadian rhythms (Sauman and Reppert, 1996;Wise et al, 2002). Connection between circadian rhythms and ecdysis is indicated by extirpation manipulations, which showed that these cells may be important for photoperiod-dependent induction of diapause occurring after pupal ecdysis (Shiga et al, 2003).…”
Section: Roles Of Neuropeptides In Eth Release Corazonin and Its Recementioning
confidence: 99%